Psychometric Properties of the Context, Input, Process, and Product (CIPP) Model for the Evaluation of Medical Ethics Education - Habibeh Ahmadipour; Amirhossein Alirezaie; Mina Mobasher (Kerman University of Medical Sciences, 2023)
Background: Medical ethics courses play a pivotal role in medical education, aiming to enhance the moral decision-making capabilities of medical students. As such, the evaluation of medical ethics education programs within medical faculties is of paramount importance for the improvement of these initiatives.Objectives: This study aimed to appraise the psychometric properties of the Context, Input, Process, Product (CIPP) evaluation model in medical ethics education.Methods: This cross-sectional study was conducted on 136 clerckship medical students, who were enrolled in a medical ethics course at Kerman University of Medical Sciences, Kerman, Iran. The participants completed a 40-item researcher-made questionnaire, which was designed based on the CIPP evaluation model. The questionnaire was divided into four distinct sections, each corresponding to the context, input, process, and product aspects of the model. The face and content validity of the instrument was established by an expert panel, consisting of 10 faculty members of medical education and medical ethics. The reliability of the questionnaire was also determined by calculating its internal consistency using Cronbach's alpha coefficient. Moreover, the construct validity of the questionnaire was assessed via confirmatory factor analysis, using the goodness of fit indices. Data were analyzed in SPSS version 19 and Lisrel 8.8.Results: The content validity index and content validity ratio of the questionnaire were measured to be 0.97 and 0.89, respectively. The internal consistency of different sections of the questionnaire ranged between 0.71 and 0.87. In the confirmatory factor analysis, the model showed acceptable goodness of fit indices.Conclusion: In this study, the psychometric properties of the CIPP evaluation model for medical ethics education were found to be acceptable and applicable.